Voter en Temps des Conflits Armés : une Lecture de la Milicianisation du Processus Électoral de 2023 à Djugu en République Démocratique du Congo - Lonu, Lotsima Prince; Warom , Janvier; Zebuandra , Mandugba Samuel (International Journal of Conflict Management, 2025)
Objective: This study aims to analyze the progress of electoral operations in an area controlled by armed groups. Methodology: we opted for a qualitative approach primarily using focus groups via WhatsApp to collect the empirical materials on which our analyses are based. Given that the activism of armed groups poses a major challenge to accessing our research field, the focus group allowed us to gather diverse data on the perceptions and experiences of local actors confronted with community conflicts and electoral results in the Djugu constituency using WhatsApp. Specifically, due to insecurity, we faced difficulties accessing certain areas; however, thanks to the focus groups, we established 5 WhatsApp groups, each consisting of 6 to 7 members, and engaged in exchanges to obtain the necessary data. We also had access to certain reports (from CENI and observers) and other documents to complement the field data. Results: The strong involvement of armed militias in the electoral process and the establishment of a special regime (state of siege) have coincided with the violation of major principles of electoral democracy. This leads to a triple crisis: a legitimacy crisis of the elected officials, a crisis of trust in the institutions, and a crisis of political representation of local populations. Contribution and Suggestion: this is a contribution to the electoral sociology of conflict-affected areas, where armed groups usurp the prerogatives of the state that they use to strengthen their control over resources, increase their dominance and power. To this end, the study suggests rethinking the electoral framework in conflict zones, by reinforcing state neutrality, securing the process, and rebuilding the local social fabric.